Innocent until his forbidden touch - Marinelli, Carol (Harlequin presents, 2022)
"PR pro Beatrice Taylor's brief is simple--clean up playboy prince Julius's image before he becomes king. A challenge made infinitely more complicated by the heat she feels for her scandalous, off-limits client! For the first time, innocent Beatrice wants to give in to wild temptation... Julius's royal duty doesn't leave room for private desire. Discovering what lies beyond Beatrice's impenetrable emotional walls shouldn't be his priority, but she fascinates him. And one stolen moment presents Julius with an impossible choice: his kingdom or the woman he can't live without!" -- Page [4] cover.